2002
DOI: 10.1207/s15516709cog2606_5
|View full text |Cite
|
Sign up to set email alerts
|

Gesture offers insight into problem‐solving in adults and children

Abstract: When asked to explain their solutions to a problem, both adults and children gesture as they talk. These gestures at times convey information that is not conveyed in speech and thus reveal thoughts that are distinct from those revealed in speech. In this study, we use the classic Tower of Hanoi puzzle to validate the claim that gesture and speech taken together can reflect the activation of two cognitive strategies within a single response. The Tower of Hanoi is a well-studied puzzle, known to be most efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 31 publications
4
65
0
6
Order By: Relevance
“…Gesture-speech mismatch occurs when gesture conveys information that is different from (although not necessarily contradictory to) the information conveyed in the speech it accompanies (Goldin-Meadow, 2003). Gesture-speech mismatches are produced by speakers of all ages and in a variety of tasks (Alibali, Bassok, Olseth, Syc, & Goldin-Meadow, 1999;Garber & Goldin-Meadow, 2002;Gershkoff-Stowe & Smith, 1997;Pine, Lufkin, & Messer, 2004;Schwartz & Black, 1996;Stone, Webb, & Mahootian, 1991) and are frequently found in teaching situations. In fact, teachers spontaneously increase the number of gesture-speech…”
Section: University Of Chicagomentioning
confidence: 99%
“…Gesture-speech mismatch occurs when gesture conveys information that is different from (although not necessarily contradictory to) the information conveyed in the speech it accompanies (Goldin-Meadow, 2003). Gesture-speech mismatches are produced by speakers of all ages and in a variety of tasks (Alibali, Bassok, Olseth, Syc, & Goldin-Meadow, 1999;Garber & Goldin-Meadow, 2002;Gershkoff-Stowe & Smith, 1997;Pine, Lufkin, & Messer, 2004;Schwartz & Black, 1996;Stone, Webb, & Mahootian, 1991) and are frequently found in teaching situations. In fact, teachers spontaneously increase the number of gesture-speech…”
Section: University Of Chicagomentioning
confidence: 99%
“…For example, discrepancy between the content of gesture and concurrent speech indicates that children are in a transitional phase in the understanding of Piagetian conservation tasks (Church & Goldin-Meadow, 1986) or arithmetic equations (Perry, Church, & Goldin-Meadow, 1988). Similar discrepancy in adults indicates that they are considering alternative strategies in a Tower of Hanoi problem (Garber & Goldin-Meadow, 2002).Gestures can provide insights into the choice of problem-solving strategies used by adults. Alibali, Bassok, Solomon, Syc, and Goldin-Meadow (1999) found that when people were asked to describe and then solve a mathematical problem, their gestures could predict the strategy they used in the solution.…”
mentioning
confidence: 99%
“…For example, discrepancy between the content of gesture and concurrent speech indicates that children are in a transitional phase in the understanding of Piagetian conservation tasks (Church & Goldin-Meadow, 1986) or arithmetic equations (Perry, Church, & Goldin-Meadow, 1988). Similar discrepancy in adults indicates that they are considering alternative strategies in a Tower of Hanoi problem (Garber & Goldin-Meadow, 2002).…”
mentioning
confidence: 99%
“…Garber and GoldinMeadow offer evidence that gesturing can actually facilitate problem-solving: people "offload" thinking into gesture as into a sketch, freeing up cognitive effort for other tasks [4]. Roth and Lawless go so far as to suggest that the act of gesturing may activate the same neuronal assemblies as the language that goes with the gesture, thereby assisting neurologically with language emergence [5].…”
Section: Prior Research On Gesture and Learningmentioning
confidence: 99%
“…The researchers classified the students as to whether they were conserving or nonconserving, and also as to whether their gestures were "concordant" or "nonconcordant;" in a subsequent teaching task, nonconserving nonconcordant children learned the most [6]. In a more recent study, Garber et al observe that gesture-speech mismatches cluster at strategic choice points in solving the Tower of Hanoi puzzle [4], suggesting that cognitive exploration of more than one solution path is taking place.…”
Section: Prior Research On Gesture and Learningmentioning
confidence: 99%